A pilot investigation into the effects of acute normobaric hypoxia, high altitude exposure and exercise on serum angiotensin-converting enzyme, aldosterone and cortisol. (June 2018) - Cooke, Mark; Cruttenden, Richard; Mellor, Adrian; Lumb, Andrew; Pattman, Stewart; Burnett, Anne; Boot, Chris; Burnip, Louise; Boos, Christopher; O'Hara, John; Woods, David
Introduction: Aldosterone decreases at high altitude (HA) but the effect of hypoxia on angiotensin-converting enzyme (ACE), a key step in the renin-angiotensin-aldosterone system, is unclear. Methods: We investigated the effects of exercise and acute normobaric hypoxia (NH, 11.0% FiO2 ) on nine participants and six controls undertaking the same exercise at sea level (SL). NH exposure lasted 5 hours with 90 minutes of submaximal treadmill walking. Blood samples for aldosterone, ACE and cortisol were taken throughout exposure and at rest during a trek to HA (5140 m) in eight separate participants. Results: There was no difference in cortisol or aldosterone between groups pre-exercise. Aldosterone rose with exercise to a greater extent at SL than in NH (post-exercise: 700 ± 325 versus 335 ± 238 pmol/L, mean ± SD, p = 0.044). Conversely, cortisol rose to a greater extent in NH (post-exercise: 734 ± 165 versus 344 ± 159 nmol/L, mean ± SD, p = 0.001). There were no differences in ACE activity. During the trek to HA, resting aldosterone and cortisol reduced with no change in ACE. Conclusions: Acute NH subdues the exercise-associated rise in aldosteroe but stimulates cortisol, whereas prolonged exposure at HA reduces both resting aldosterone and cortisol. As ACE activity was unchanged in both environments, this is not the mechanism underlying the fall in aldosterone.